Towards developing an intergrated maturity model framework for managing an enterprise business intelligence - Chuah, M.H.; Wong, K.L. (2012)
There has been a great deal of recent interest that is driving research and development in the area of Business Intelligence (BI),but the issues regarding the implementation of enterprise scale of BI is still concern among BI academics and practitioners.Therefore, an Enterprise Business Intelligence Maturity Model(EBI2M) is proposed to serve as useful guideline for enterprises which are planning or undertaking large scale BI initiatives.In this paper, the author utilizes a Delphi study to conduct two stages of enquiries with a panel of BI experts, and then refines the research into a preliminary EBI2M model.